Analisis Jual Beli Akun Game Rise Of Kingdom di Komunitas Grup Facebook dalam Perspektif Etika Bisnis Islam - Ryo Ahmad Alpandi; Budi Ihsan; Sri Yuli Astuti (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
The phenomenon of buying and selling online game accounts, particularly Rise of Kingdoms (RoK), has become a significant economic commodity on social media platforms such as Facebook. However, this practice often exists in a gray area, both in terms of developer policies and Islamic law (Sharia). This article aims to analyze such transaction practices from the perspective of Islamic Business Ethics. The research method employed is a descriptive qualitative approach, utilizing literature review and virtual observation. The results indicate that the buying and selling of RoK accounts is permissible as long as it fulfills the pillars and principles of a valid sale. However, it becomes problematic when elements of gharar (uncertainty) and tadlis (deception), particularly regarding account specifications, are involved.